Work-related exposure to violence or threats and risk of mental disorders and symptoms: a systematic review and meta-analysis - Rudkjoebing, Laura A; Bungum, Ane Berger; Flachs, Esben Meulengracht; Eller, Nanna Hurwitz; Borritz, Marianne; Aust, Birgit; Rugulies, Reiner; Rod, Naja Hulvej; Biering, Karin; Bonde, Jens Peter (Scandinavian Journal of Work, Environment & Health, 2020)
' ' OBJECTIVE ': 'This review aimed to examine systematically the epidemiological evidence linking work-related exposure to violence and threats thereof with risk of mental disorders and mental ill-health symptoms. ' ' METHODS ': 'We searched PubMed, EMBASE, PsycINFO and Web of Science to identify original studies that provide quantitative risk estimates. The evidence was weighted according to completeness of reporting, potential common method bias, and bias due to differential selection and drop out, selective reporting, and misclassification of exposure and outcome. ' ' RESULTS ': 'We identified 14 cross-sectional and 10 cohort studies with eligible risk estimates, of which 4 examined depressive disorder and reported an elevated risk among the exposed [pooled relative risk (RR) 1.42, 95% confidence interval (CI) 1.31–1.54, I2=0%]. The occurrence of depressive and anxiety symptoms, burnout and psychological distress was examined in 17 studies (pooled RR 2.33, 95% CI 3.17, I2=42%), and 3 studies examined risk of sleep disturbance (pooled RR 1.22, 95% CI 1.09–1.37, I2=0%). In most studies, common method bias and confounding could not be ruled out with confidence and strong heterogeneity in most outcome definitions invalidate the strict interpretation of most pooled risk estimates. ' ' CONCLUSION ': 'The reviewed studies consistently indicate associations between workplace violence and mental health problems. However, due to methodological limitations the causal associations (if any) may be stronger or weaker than the ones reported in this study. Prospective studies with independent and validated reporting of exposure and outcome and repeated follow-up with relevant intervals are highly warranted.
Keywords: anxiety; burnout; depression; exposure; mental disorder; meta-analysis; psychological distress; review; sleep disturbance; systematic review; threat; violence; work-related exposure; workplace violence